Economic thoughts on COVID‐19 for Canadian food processors. (9th May 2020) - Hailu, Getu
Abstract: In this paper, I explore the potential effects of the COVID‐19 pandemic on Canadian food processors. First, COVID‐19 may have an impact on food processing economic activities because of supply and demand shocks. Second, the impact of COVID‐19 on food processing may depend on the type of products and the size of the processors. The effects of measures taken by the government to flatten the epidemiological curve on the economic activities of the food processing sector are uncertain. Abstrait: Dans cet article, j'explore les effets potentiels de la pandémie de la COVID‐19 sur les transformateurs alimentaires canadiens. Premièrement, la COVID‐19 peut avoir un impact sur les activités économiques de transformation des aliments en raison des chocs de l'offre et de la demande. Deuxièmement, l'impact de COVID‐19 sur la transformation des aliments peut dépendre du type de produits et de la taille des transformateurs. Les effets des mesures prises par le gouvernement pour aplanir la courbe épidémiologique sur les activités économiques du secteur de la transformation alimentaire sont incertains.